R-loop landscape in mature human sperm: Regulatory and evolutionary implications - Scheuren, Maurice; Möhner, Jonas; Zischler, Hans (Frontiers in Genetics, 2023)
R-loops are three-stranded nucleic acid structures consisting of an RNA:DNA hybrid and a displaced DNA strand. While R-loops pose a potential threat to genome integrity, they constitute 5% of the human genome. The role of R-loops in transcriptional regulation, DNA replication, and chromatin signature is becoming increasingly clear. R-loops are associated with various histone modifications, suggesting that they may modulate chromatin accessibility. To potentially harness transcription-coupled repair mechanisms in the germline, nearly the entire genome is expressed during the early stages of male gametogenesis in mammals, providing ample opportunity for the formation of a transcriptome-dependent R-loop landscape in male germ cells. In this study, our data demonstrated the presence of R-loops in fully mature human and bonobo sperm heads and their partial correspondence to transcribed regions and chromatin structure, which is massively reorganized from mainly histone to mainly protamine-packed chromatin in mature sperm. The sperm R-loop landscape resembles characteristic patterns of somatic cells. Surprisingly, we detected R-loops in both residual histone and protamine-packed chromatin and localize them to still-active retroposons, ALUs and SINE-VNTR-ALUs (SVAs), the latter has recently arisen in hominoid primates. We detected both evolutionarily conserved and species-specific localizations. Comparing our DNA-RNA immunoprecipitation (DRIP) data with published DNA methylation and histone chromatin immunoprecipitation (ChIP) data, we hypothesize that R-loops epigenetically reduce methylation of SVAs. Strikingly, we observe a strong influence of R-loops on the transcriptomes of zygotes from early developmental stages before zygotic genome activation. Overall, these findings suggest that chromatin accessibility influenced by R-loops may represent a system of inherited gene regulation.